Causal Association Between Inflammatory Bowel Disease and Psoriasis: A Two-Sample Bidirectional Mendelian Randomization Study - Li, Yajia; Guo, Jia; Cao, Ziqin; Wu, Jianhuang (Frontiers in Immunology, 2022)
Background: Previous observational studies have found an association between inflammatory bowel disease (IBD) and psoriasis. Using the mendelian randomization (MR) approach, we aim to determine whether there was a causal association between IBD and psoriasis. Methods: We performed a two-sample MR with the genetic instruments identified for IBD and its main subtypes, Crohn’s disease (CD) and ulcerative colitis (UC), from a genome-wide association study (GWAS) involving 25,042 cases with an IBD diagnosis and 34,915 controls. Summarized data for psoriasis were obtained from different GWAS studies which included 4510 cases and 212,242 controls without psoriasis. Causal estimates are presented as odds ratios (ORs) with 95% confidence intervals (CIs). Results: The overall outcome of MR analysis was to demonstrate that genetic predisposition to IBD was associated with an increased risk of psoriasis (OR: 1.1271; 95% CI: 1.0708 to 1.1864). Psoriatic arthritis (PsA) had a significant association with total IBD (OR: 1.1202; 95% CI: 1.0491 to 1.1961). Casual relationship was also identified for CD-psoriasis (OR: 1.1552; 95% CI: 1.0955 to 1.2182) and CD-PsA (OR: 1.1407; 95% CI: 1.0535 to 1.2350). The bidirectional analysis did not demonstrate that a genetic predisposition to psoriasis was associated with total IBD, although psoriasis showed association with CD (OR: 1.2224; 95% CI: 1.1710 to 1.2760) but not with UC. A genetic predisposition to PsA had a borderline association with IBD (OR: 1.0716; 95% CI: 1.0292 to 1.1157) and a suggestive association with CD (OR: 1.0667; 95% CI: 1.0194 to 1.1162). Conclusion: There appears to be a causal relationship between IBD and psoriasis, especially for PsA, but for psoriasis and IBD, only total psoriasis and PsA were associated with CD. Understanding that specific types of psoriasis and IBD constitute mutual risk factors facilitates the clinical management of two diseases.